(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess physical and psychological changes in patients with thyroid cancer after I-131 therapy and to identify associated factors. Methods: A cross-sectional descriptive study was conducted at Bach Mai Hospital from July 1 to November 30, 2025, among 140 patients with thyroid cancer who had undergone I-131 treatment, using convenience sampling. Data were collected using a general information questionnaire and the THYCA-QoL scale and analyzed with SPSS version 20.0. Results: The mean overall physical-psychological change score was 41.0 ± 12.1 points (scale 0-100), ranging from 24 to 74 points. The most common symptoms were muscle and/or joint pain (35.7%), sudden fatigue (30.7%), palpitations (23.6%), anxiety (23.5%), hoarseness (22.9%), and leg cramps (22.9%). The overall score differed significantly by occupation (F = 3.78; p = 0.001) and educational level (F = 4.44; p < 0.05). Patients receiving high-dose I-131 had significantly higher change scores than those receiving low-dose treatment (43.51 ± 11.40 points vs. 37.35 ± 12.27 points; p = 0.003). Time since thyroidectomy showed a weak positive correlation with the overall score (r = 0.178; p = 0.04). No statistically significant associations were found between the overall score and sex, marital status, payment method, or comorbidities (p > 0.05). Conclusion: Patients with thyroid cancer after I-131 therapy experience moderate levels of physical and psychological changes, with prominent musculoskeletal symptoms, fatigue, and anxiety. Long-term follow-up, symptom management, and psychological support are recommended, particularly for high-risk groups.